MIGRANTS AND REFUGEES. ON THE WAY TO PARTNERSHIP - Niewdana, Agnieszka; Cekiera, Rafał (No Limits, 2022)
The issue of migration is one of the most important research topics today, also among sociologists. For at least a few years now, we have been observing an increase in migration movements. What are their causes? What are the consequences? These questions have been addressed by a scientist specialising in the sociology of migration, religion, and the analysis of contemporary cultural transformations.